Kunst aus Quebec/Canada. - Galerie Clara Maria Sels, Düsseldorf (Düsseldorf : Galerie Clara Maria Sels, 1992)
Lipke, Kathryn ; Sullivan, Françoise ; Fournelle, André ; Widgery, Catherine ; Gould, Trevor ; Penserini, Francesca ; Moore, David ; Lammerich, Yvonne ; Couvreur, Daniel ; Farley, Denis
Kunst aus Quebec/Canada, Galerie Clara Maria Sels, Düsseldorf, 1992
boek